Telaah Hukum Islam terhadap Nasab Anak - Sakirman, Sakirman (Hunafa: Jurnal Studia Islamika, 2015)
The classical scholars of jurisprudence agreed that nasab child has only nasab relationship to his parents, nasab determination is one of the most important rights of a child and is something that a lot of impact on the child's personality and future. Fiqh scholars say that the concept nasab is one solid foundation in building a domestic life that can bind between individuals based on the unity of blood. In Indonesia Islamic law, the problem of the origin of the child, there are several different legal provisions. It is influenced by a plurality of the nation, especially in terms of religion and customs, the applicable law is varied. There are laws, ie Islamic law (fiqh) formulated in a fixed rule the Islamic Law Compilation (KHI).